Local community atitudes’ towards tourism development in Tioman Island / Siti Aisah Abas - Abas, Siti Aisah (2013)
Tourism industry has been recognised as the symbol to help the local community especially in changing the economic and atmosphere due to the ability to generate income, employment as well improve the standard of living. The attitudes of the local community can directly affect the development of the tourism industry. Positive attitudes from the local residents not only can help in boosting tourists’ satisfaction levels at the same time it contributes to word-of-mouth promotion among international tourist. In order to ensure the success of the tourism planning, the involvement and the participation of the local communities in the area is pertinent. This study endeavours on local community attitudes’ toward tourism development in Tioman Island. The findings on this study indicated that the local community who obtained the personal benefit from tourism development will support for future tourism development as well as who perceived the positive impact on the tourism development. However, from the finding revealed that the local community who perceived negative impact from tourism activities also support the tourism development in the future due to the reliance on this sector as their main income. The role of perceived tourism impact as the moderator between the relationship between personal benefit from tourism and the future attitudes from tourism development become the contribution of this study.